Does combination therapy work in chronic thromboembolic pulmonary hypertension?. (August 2020) - van Thor, M.C.J.; Snijder, R.J.; Kelder, J.C.; Mager, J.J.; Post, M.C.
Highlights: Long-term overall survival of CTEPH patients receiving PH-specific medial therapy is very reasonable. Despite worse baseline characteristics at baseline, combination therapy showed similar survival as monotherapy. Combination therapy strategy showed no difference in survival outcome. Abstract: Objective: The current experience with combination therapy in chronic thromboembolic pulmonary hypertension (CTEPH) is limited. We present the first survival results up to 5 years for dual combination therapy versus monotherapy in CTEPH. Methods: All consecutive, non-operated CTEPH or residual PH after pulmonary endarterectomy patients treated with PH-specific medical therapy between January 2002 and November 2019 were included. We report and compare survival between monotherapy and (upfront or sequential) dual combination therapy until five years after medication initiation. Results: In total, 183 patients (mean age 65 ± 14 years, 60% female, 66% WHO FC III/IV, 86% non-operated) were included, of which 83 patients received monotherapy and 100 patients received dual combination therapy. At baseline, patients receiving combination therapy had a higher NT-proBNP (p = 0.02) mean pulmonary artery pressure (p = 0.0001) and pulmonary vascular resistance (p = 0.02), while cardiac index was lower (p = 0.03). Total follow-up duration was 3.3 ± 1.8 years, during which 31 (17%) patients died. Estimated 1-, 3- and 5-year survival for monotherapy were 99%, 92% and 79%, respectively. For combination therapy percentages were 98%, 89% and 70%, respectively. Survival did not significantly differ between both groups (p = 0.22). Conclusion: Survival up to 5 years for patients treated with combination therapy, regardless of the combination strategy, was similar as patients with monotherapy, despite worse clinical and haemodynamic baseline characteristics.